PENINGKATAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN PENGUATAN LEARNING ORGANIZATION (LO) DAN KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH - Yohana Erna Yani Astuti; Rais Hidayat; Farida Wulandari (JURNAL MANAJEMEN PENDIDIKAN, 2021)
IMPROVING  TEACHER  ORGANIZATIONAL  CITIZENSHIP BEHAVIOR  BY  STRENGTENING OF LEARNING  ORGANIZATION AND PRINCIPAL TRANSFORMATIONAL LEADERSHIPThis study is intended   to empirically determining the relationship between  Strengthening of Learning Organization and Principal Transformational Leadership towards Organizational Citizenship Behavior (OCB). The population in this study were permanent teachers of the Private Junior High Schools foundations accredited A, in Central Bogor Distric, Bogor City. There were 102 teachers who were taken by porpotional random sampling. The method using was  correlational method. The hypothesis testing was carried out using parametic statistical analysis in the form of simple and multiple   linear,   regression analysis, simple and multiple correlation analysis where the significant levels of α = 0,05  and  0,01.  This  research  resulted  in  four  conclutions and  followed  by  the SITOREM analysis stage. Firstly, there was very significant possitive corellation between the Strengthening of the Learning Organization and   the OCB. It was indicated by the corellation coefficient ry1=0,522, supported by the regression equation Ŷ = 60,9380+ 0,4019X1 and the determination coefficient r2y=0,2724. Secondly,  there  was  very  significant  possitive  corellation  between  principal transformational  leadership  and  the OCB. It was indicated by the corellation coefficient  ry1=0,493,  supported  by  the  regression  equation  Ŷ  =  63,8397  + 0.4146X2,  and the determination coefficient r2y=0,2430. Thirdly, there was very significant   possitive   corellation   between   both   strengthening   of   Learning Organization and principal transformational   leadership   towards   the OCB. It was indicated by the corellation coefficient ry.12=0,541, supported by the regression equation Ŷ = 54,4963 + 0.2698X1 + 0.1870X2, and the determination coefficient r2y=0,2927. Fourthly, OCB could be improved by strengthening the Learning Organization and principal transformational    leadership, both separately or altogether. It  can be concluded that OCB can be improved by strengthening   Learning   Organization   and   principal   transformational leadership. The results of the SITOREM analysis ftgured out that the components of strengthening  of  learning  organization,  principal  transformational  leadership, and OCB were gaining 13 good indicators that they could be maintained, which were: (1) Mental Models, (2) Inspirational Motivation, (3) Intellectual Stimulation, (4) Concientousness, (5).Personal Mastery, (6) Sportmanship, (7) Systemic Thinking, (8)  Contingen  Reward, (9)  Idealized  Influence,  (10)  Courtesy,  (11) Teams  Learning,  (12) Shared  Vision,  (13)  Individualized Consideration. Meanwhile, there were 2 indicators those were still needed to be improved, namely: (1) Altruisme and (2) Civic Virtue,